DNA sequencing validation of PCR-RFLP technique for evaluating butyrophilin-like 2 rs2076530 polymorphism in Iranian patients with sarcoidosis - Javadi, Alireza; Zarei, Masoud; Pourabdollah, Mihan; Sadr, Makan; Kiani, Arda; Abedini, Atefeh; Shamaei, Masoud (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2022)
Background: Sarcoidosis is a multifactorial immune disorder with uncertain origin. A single nucleotide polymorphism (G→A, rs2076530) in the butyrophilin-like 2 (BTNL2) gene results in the formation of truncating protein. This study aimed to genotype the predisposition of the BTNL2 rs2076530 polymorphism in Iranian patients with sarcoidosis using the newly designed RFLP technique.Materials and Methods: In this study, 80 patients with sarcoidosis and 80 healthy individuals were included. The rs2076530 polymorphism of the BTNL2 gene was genotyped using the PCR-RFLP method by AvrII restriction enzyme and confirmed by DNA sequencing (Capillary electrophoresis 3130, ABI).Results: A statistical significant was observed in proportion of patient's AA (67.9%) in comparison to AA (40.7%) (OR=3.07,95%CI:1.40-6.7, P=0.004) in controls. Also, a significant difference was statistically found between the A (62.5%) in subjects and A (43.8%) allele in controls (OR=2.14,95%CI:1.37-3.35, P=0.001). However, no statistical difference was seen between cases and controls based on AA and AG proportion.Conclusion: Our data emphasized the association of the BTNL2 rs2076530 A allele with sarcoidosis susceptibility in Iranian patients. The newly designed PCR-RFLP method for the rs2076530 A allele could also be applicable in resource-limited countries.